Detection of Efflux Pumps Gene and Relation with Antibiotics Resistance in Uropathogenic Escherichia Coli (UPEC) Isolated from Patients with Cystitis - Ali, Saher Amer; Al-Dahmoshi, Hussein O.M. (Iraqi Journal of Science, 2022)
Background: In recent years, the multidrug-resistant (MDR) Escherichia coli has increased in urinary tract infections (UTIs). One of the highly distributed chromosomally encoded traits of resistance is efflux pump. The current study aimed to investigate the most common members of 5 classes of efflux pumps among uropathogenic E. coil isolates.Methodology: E. coli isolates were isolated using conventional bacteriology tests   and confirmed by the uidA gene. An antibiotic susceptibility test has been done against 25 antibiotics using disc diffusion method. Efflux pump genes have been examined via polymerase chain reaction. Biofilm formation was investigated by a 96-well polystyrene microtiter plate.Results: In total, 50 E. coli isolates were collected from UTIs. All isolates were resistant to amoxicillin, ceftazidime, and cefotaxime, while all isolates were sensitive to imipenem.  Also, 19 (38%) E. coli isolates were non-MDR, while 31 (62%) were MDR.  The frequency rates of different efflux pump genes ranged from 66% to 100%. The biofilm formation results indicated that 98% of isolates were biofilm former while 2% were non-biofilm. In total, 60% was weak biofilm, 24% was moderate, and 14% was strong biofilm former.Conclusion: The current study concludes that all efflux pumps may be highly associated with resistance to amoxicillin, cefotaxime, and ceftazidime and moderately associated with cefepime, ceftriaxone, and cefixime and may be unrelated to the resistance of other studied antibiotics or the concentration of these antibiotics inadequate to induce the expression of these pumps. Additionally, biofilm formation was highly related to the presence of study pumps.